Development of an Aquatic Conservation Model in Agam Regency through Local Wisdom Based Community Empowerment to Improve Fishermen's Economies - Murhenna Uzra; Sri Yenica Roza; Rezi Junialdi; Siska Handayani; Irwandi Irwandi (The Future of Education Journal, 2026)
Agam Regency has significant aquatic resource potential; however, various issues such as declining water environmental quality, insufficiently controlled reso urce exploitation, and low community involvement in conservation activities pose challenges to achieving sustainable water resource management. This study aims to develop a water conservation model for Agam Regency through community empowerment (Bado and Zulkifli, 2021), based on local wisdom as an effort to improve the economic well-being of fishers. The research method employed is a mixed methods approach, combining qualitative and quantitative methods. Data were collected through field observations, in-depth interviews, Focus Group Discussions (FGDs), and the distribution of questionnaires to fishing communities, traditional leaders, local government officials, and other relevant stakeholders. Data analysis was conducted descriptively, participatively, and using a model development approach. The research results show that the local wisdom still practiced by the community has great potential to serve as a foundation for the management and conservation of aquatic resources. Lakoy et al. (2021) stated that the development of the conservation model was carried out through strengthening community institutions, enhancing fishers' capacity, implementing customary-based regulations, diversifying productive economic enterprises, and fostering collaboration among communities, the government, and related institutions. The resulting model places the community as the primary actor in the management of aquatic resources while continuing to take ecological, social, cultural, and economic aspects into consideration. The implementation of this model is expected to help ensure the sustainability of aquatic resources, increase public awareness of conservation, strengthen local institutions, and sustainably improve the income and welfare of fishers.